2009
DOI: 10.1163/156853909x410766
|View full text |Cite
|
Sign up to set email alerts
|

Territorial contests within and between two species of flies (Diptera: Richardiidae) in the wild

Abstract: Males and females of two syntopic phytophagous fly species (O. nitens and O. ferruginea, Diptera: Richardiidae) compete over small ephemeral feeding territories. We assessed fight frequency of both sexes of two species in the wild, and the simultaneous effects of potential fight asymmetries, sex and species, on the outcome of territorial contests in relation with resident status. Our results showed that residents won most of the fights, although the proportion of fights won by the resident depended on the sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This is interesting since the two species potentially have different burrow structures (H.L.C. 2016, personal observation) which would represent different resource qualities and should, therefore, affect the male's decision on who to fight [ 7 ]. However, T. elegans evicted both conspecifics and heterospecifics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is interesting since the two species potentially have different burrow structures (H.L.C. 2016, personal observation) which would represent different resource qualities and should, therefore, affect the male's decision on who to fight [ 7 ]. However, T. elegans evicted both conspecifics and heterospecifics.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on shore birds demonstrated a decline in numbers after events resulting in local habitat loss, as a result of increased intraspecific and interspecific competition [ 5 , 6 ]. Increased competition is costly as it results in reduced fitness or even survivorship for individuals [ 7 ] or even entire species [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A residency advantage to interspecific territorial disputes has been demonstrated in several insects (Resende, ; e.g. Becerril‐Morales & Macias‐Ordonez, ), but has seldom been tested explicitly in vertebrates (but see Smith & Pough, for an example). Understanding the role of residency in affecting interspecific aggression is important for understanding interspecific interactions because it may potentially explain why some species consistently dominate heterospecifics in aggressive and competitive interactions.…”
Section: Introductionmentioning
confidence: 99%